Unusual case of bilateral hand weakness. Issue 6 (17th August 2017) - Datta, Sayan; Cosgrove, Jeremy; Alam, Taimour; Ford, Helen L
Abstract : A 35-year-old man presented with myalgia and bilateral hand weakness, 3 days after the onset of lethargy, fevers and rigours. The hand weakness caused functional impairment including difficulty pressing keys on his mobile phone. On examination, there was mild bilateral hand weakness with normal reflexes. His serum creatine kinase was mildly raised at 503 U/L (24–195), viral PCR throat swab was negative and electromyogram showed subtle myopathic changes in the distal forearm muscles. Nerve conduction studies found no evidence of neuropathy. Forced vital capacity was reduced on admission (1.5 L) but improved within 24 hours (2.3 L). We gave supportive intravenous fluids and his weakness improved within 48 hours. He was discharged and reported that the weakness had fully resolved within weeks. The diagnosis was viral myositis. Distal forearm myositis rarely follows H1N1 influenza in adults but is an important differential for postinfective neurological symptoms.